Spontaneously recovered severe thrombocytopaenia following zoledronic acid infusion for osteoporosis. (3rd February 2016) - Kulkarni, Pooja; Cushman, Terra; Donthireddy, Vijayalakshmi; Rao, Sudhaker
Abstract : Zoledronic acid is widely used for the treatment of various skeletal disorders. While acute phase reactions are commonly seen, hypocalcaemia, femoral shaft fractures, osteonecrosis of the jaw and renal failure are rare. Two cases of fatal thrombocytopaenic purpura have been reported following zoledronic acid infusion. We report a case of non-fatal thrombocytopaenia with spontaneous recovery. A 70-year woman with osteoporosis participated in a research study. Complete blood and platelet counts prior to zoledronic acid infusion were normal (138 000/µL), but had declined slightly from 185 000/µL 2 years ago. One year after the first zoledronic acid infusion, her platelet count declined to 50 000/µL without any clinical manifestations, and rose slowly returning to normal (156 000/µL) over the next 1 year. Extensive evaluation did not reveal any specific abnormalities, and the pathogenesis of her transient severe thrombocytopaenia after two infusions of zoledronic acid remains unclear.